Risk Factors and Complications in Herpes Zoster Patients at Dr. Soetomo General Academic Hospital, Surabaya - Nadiva, Shafa Karin; Hidayati, Afif Nurul; Basuki, Mudjiani; Machin, Abdulloh (Universitas Airlangga, 2024)
Highlights: The highest distribution of herpes zoster patients’ age and gender was between 46-55 years old and females. The highest distribution of herpes zoster patients’ complications was post-herpetic neuralgia. Abstract Introduction: Herpes zoster (HZ) is a painful rash confined to a dermatome resulting from the reactivation of the varicella-zoster virus (VZV). Factors that increase the risk of HZ include age, sex, prior varicella infection, immunocompromised conditions, SARS-CoV-2 infection, and varicella vaccination. Potential complications of Herpes zoster may encompass post-herpetic neuralgia (PHN), Ramsay Hunt syndrome, meningoencephalitis, vasculopathy, and varicella pneumonia. This study aimed to identify risk factors and complications associated with Herpes zoster and to enhance preventive measures to decrease the incidence of Herpes zoster at Dr. Soetomo General Academic Hospital, Surabaya, Indonesia. Methods: This descriptive, retrospective analysis utilized secondary data from the medical records of Herpes zoster patients at the Dermatology Clinic of Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, from 2019 to 2021. Data analysis used the International Business Machines Corporation (IBM) Statistical Package for the Social Sciences (SPSS) version 25.0. Results: Out of 105 cases, Herpes zoster was more frequently observed in females (61 patients, 58.1%), with the highest occurrence found in the 46–55 years old age group (33 patients, 31.04%). The thoracic nerve was the most frequently involved (58 patients, 55.2%). Hypertension emerged as the most prevalent risk factor (26 patients, 24.7%), followed by diabetes mellitus/DM (15 patients, 14.3%) and autoimmune disorders (7 patients, 6.7%). Most patients had no comorbidities (33 patients, 31.4%). Post-herpetic neuralgia was the most frequent complication (19 patients, 18.1%), while 78 patients (74.3%) reported no complications. Conclusion: Herpes zoster was more prevalent among females, with hypertension being the most significant risk factor and post-herpetic neuralgia the most common complication.